Exploiting ubiquitin ligase cereblon as a target for small-molecule compounds in medicine and chemical biology - Ito, Takumi; Yamaguchi, Yuki; Handa, Hiroshi (Cell chemical biology, 2021)
Cereblon (CRBN), originally identified as a gene associated with intellectual disability, was identified as primary target of thalidomide. Accumulating evidence has shown that CRBN is a substrate receptor of Cullin Ring E3 ubiquitin ligase 4 (CRL4) containing DDB1, CUL4, and RBX1, which recognizes specific neosubstrates in the presence of thalidomide or its analogs and induces their ubiquitination and proteasomal degradation. A set of small-molecule, CRBN-binding drugs are known as molecular glue degraders because these compounds promote the interaction between CRBN and its neosubstrates. Moreover, CRBN-based proteolysis-targeting chimeras, heterobifunctional molecules hijacking CRBN and inducing degradation of proteins of interest, have emerged as a promising modality in drug development and are being actively investigated. Meanwhile, the original functions and regulations of CRBN are still largely elusive. In this review, we describe key findings surrounding CRBN since its discovery and then discuss a few unanswered issues. [Display omitted] Cereblon is a component of the ubiquitin ligase complex whose substrate specificity can be manipulated by small-molecule compounds, such as thalidomide and its derivatives. Ito et al. provide a comprehensive review of cereblon from its discovery to the latest topics including its use for drug development and other medical applications.